Dengue fever in Northern Pakistan: The Hepatic Implications - Syed Irfan Ahmed, Muhammad Ali Khalid, Haider Zaigham Baqai, Syed Farhan Ali, Zubair Ahmad Ranja (Journal of Rawalpindi Medical College, 2009)
Background: To gauge the clinical spectrum of dengue fever in northern Pakistan and to assess its hepatic implications Methods: This prospective study was conducted at Rawalpindi General Hospital (now BBH), Rawalpindi from 1st Oct 2006 to 31st Dec 2008. It included all 264 patients suffering from dengue fever who presented during this period. Dengue infection was suspected if two or more of the following features in addition to fever were present: headache, retro-orbital pain, myalgias/arthralgias, scarlet/maculopapular rash, vomiting/epigastric pain and haemorrhagic manifestations. Blood samples were sent for dengue virus IgM. A blood complete picture, liver function tests, serum urea and creatinine, and urine R/E were also obtained. Specific evidence of liver involvement was also sought on examination. Results: The 264 patients comprised of 146 males and 118 females. Age of patients ranged from 14 to 80 years. 220 patients were seen in the last three months of 2006, the time of the dengue epidemic. Fever and myalgias were present in all patients. Vomiting was seen in 223 (85%) and abdominal pain in 163 (62%) patients. A skin rash was present in 148 (56%) while 56 (21%) complained of joint pains and 53 (20%) of retro-orbital pain. 26 (10%) patients had a bleeding disposition and jaundice was noted in 6 (2%). Leukopenia and thrombocytopenia were present in all patients, while 254 (96%) had proteinuria. ALT was elevated in 163 (62%) and AST was raised in 135 (51%) patients. Conclusion: The liver is affected in a large number of cases of dengue fever. Liver function tests are useful to evaluate the degree of liver damage and markers such as AST and ALT may be used as parameters to assess severity